Fragmented narrative and diaristic writing in the Spanish literature of democracy (Castilla. Estudios de Literatura, 2022)
The aim of this article is to analyse the fragmentary nature of the discourse that can be found in certain personal diaries in the Spanish context of democracy. In these diaries, the fragment conditions the construction of the everyday narrative. At the same time, it is linked to the introduction of certain generic formats related to essayistic literature. This dialogue between fragment and narrative makes the literary diary one of the most innovative texts in recent Spanish literature, which will be developed in this work by analysing the diaries of Trapiello, Jiménez Lozano, Freixas and Uriarte, among others.
Keywords: personal diary; literary diary; fragmented narrative; comtemporary Spanish literature; theory of autobiography